Contribuição de mulheres para o ensino e pesquisa da matemática - Souza, Marcela Eduarda Belini de (Universidade Federal de São Carlos, 2024)
This study highlights the contributions of ten women mathematicians who made significant marks on the field. Hypatia of Alexandria was a pioneer in teaching and producing scientific knowledge, while Maria Gaetana Agnesi wrote one of the first comprehensive manuals on calculus. Marie-Sophie Germain made advances in number theory and elasticity, and Sofia Kovalevskaya was the first woman to earn a Ph.D. in mathematics, contributing to differential equations and mechanics. Emmy Noether revolutionized abstract algebra with her theorem, which is fundamental to modern physics. Katherine Johnson was crucial in the calculations for NASA’s space missions, while Maria Laura Leite Lopes contributed especially to the teaching of mathematics in Brazil. Evelyn Boyd Granville excelled in space computing, and Karen Uhlenbeck became the first woman to win the Abel Prize. Maryam Mirzakhani, the first woman to receive the Fields Medal, made breakthroughs in geometry and dynamical systems. This study acknowledges the importance of these mathematicians and their lasting impact on the field.
Contribution of women to mathematics teaching and research
Keywords: Mulheres matemáticas; Contribuições científicas; Avanços matemáticos; Legado acadêmico; Female mathematicians; Scientific contributions; Mathematical advances; Academic legacy; CIENCIAS EXATAS E DA TERRA::MATEMATICA